1998
DOI: 10.1126/science.280.5372.2095
|View full text |Cite
|
Sign up to set email alerts
|

Perennial Antarctic Lake Ice: An Oasis for Life in a Polar Desert

Abstract: The permanent ice covers of Antarctic lakes in the McMurdo Dry Valleys develop liquid water inclusions in response to solar heating of internal aeolian-derived sediments. The ice sediment particles serve as nutrient (inorganic and organic)-enriched microzones for the establishment of a physiologically and ecologically complex microbial consortium capable of contemporaneous photosynthesis, nitrogen fixation, and decomposition. The consortium is capable of physically and chemically establishing and modifying a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
208
1
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 341 publications
(217 citation statements)
references
References 14 publications
7
208
1
1
Order By: Relevance
“…This is consistent with the findings of , who also showed that the net primary productivity (inferred from oxygen evolution rates) in C. simplex was highest in pelagic and lowest in sea-ice conditions during short-term acclimation experiments. The results are also consistent with in-situ measurements from an Antarctic ice-covered lake (Priscu et al, 1998). Further, thẽ 8-fold difference in carbon productivity rates between cells from the sea-ice and pelagic treatments is almost identical to that measured by Boyd et al (1995), where carbon productivity rates in sea-ice algae were eight times lower than those in the surrounding water column.…”
Section: Discussionsupporting
confidence: 86%
“…This is consistent with the findings of , who also showed that the net primary productivity (inferred from oxygen evolution rates) in C. simplex was highest in pelagic and lowest in sea-ice conditions during short-term acclimation experiments. The results are also consistent with in-situ measurements from an Antarctic ice-covered lake (Priscu et al, 1998). Further, thẽ 8-fold difference in carbon productivity rates between cells from the sea-ice and pelagic treatments is almost identical to that measured by Boyd et al (1995), where carbon productivity rates in sea-ice algae were eight times lower than those in the surrounding water column.…”
Section: Discussionsupporting
confidence: 86%
“…Long regarded as essentially barren of life, recent investigations of Antarctic environments have revealed considerable microbial activity (e.g. Priscu et al 1998). The Archaea and Bacteria that have adapted to these extreme conditions are some of the best candidates for terrestrial analogues of potential extraterrestrial life; understanding their adaptive strategy, and its limitations, will provide deeper insight into fundamental constraints on the range of habitable environments (Cavicchioli 2002;DasSarma 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Multidisciplinary approaches have been undertaken to investigate relevant cyanobacteria and algae from various sources including polar desert (Priscu et al, 1998). The taxonomic features, physiological properties and ecological adaptation of these organisms as well as the potentiality to use them in desert reclamation have been discussed (Garcia-Pichel et al, 2001;Liu et al, 2001;Potts, 2000).…”
Section: Introductionmentioning
confidence: 99%